Galaxy overdensities around 3C radio galaxies and quasars at 1 < z < 2.5 revealed by Spitzer 3.6/4.5 µm and Pan‐STARRS. Issue 7 (29th September 2017) - Ghaffari, Z.; Westhues, Ch.; Haas, M.; Chini, R.; Willner, S. P.; Ashby, M. L. N.; Wilkes, B. J.
Abstract : Luminous radio sources are thought to lie in galaxy clusters or proto‐clusters. The complete sample of 64 high‐redshift 3C sources at 1 < z < 2.5 has been mapped with the Spitzer Space Telescope . The IRAC 3.6 and 4.5 µm 5 σ detection limit of 4 µJy (22.4 AB mag) allows us to search for the brightest candidate cluster member galaxies associated with the 3C sources. To remove the contamination of foreground stars and galaxies along the lines of sight toward the 3C sources, we apply color cuts: the removed sources satisfy either the IRAC1/2 cut [3.6]–[4.5] < −0.3 or the Pan‐STARRS/IRAC cut i − [4.5] < 0.5 if detected by Pan‐STARRS. For both selection methods, about half of the 3C radio sources show significant overdensities (> 3 σ ) within 30 ″ (∼250 kpc) projected distance from the radio source compared to the surrounding galaxy densities measured in the 50–120 ″ annulus. The Pan‐STARRS/IRAC cut reveals higher average overdensities than the IRAC1/2 cut and also a decline of overdensities at z > 1.4. To infer the nature of the cluster members, we rerun the analysis using a stronger IRAC1/2 cut [3.6]–[4.5] < −0.1, which removes 1 < z < 1.4 passive ellipticals but not star‐forming galaxies. For the strong cut, the overdensities, on average, completely disappear at 1 < z < 1.4. We therefore suggest that the 4.5 µm detected cluster member galaxies are mainly passive ellipticals.